Relating the gospels: memory, imitation and the Farrer hypothesis - Eve, Eric (Library of New Testament studies, 2021)
"Relating the Gospels examines the synoptic problem and argues that the similarities between the gospels of Matthew and Luke outweigh the objections commonly raised against the theory that Luke used the text of Matthew in composing his gospel"--